ANALISIS KINERJA KEUANGAN DITINJAU DARI RASIO LIKUIDITAS PROFITABILITAS DAN PERTUMBUHAN PADA LP3I COURSE CENTER JAKARTA - Mujtabah Fatururrahman (POLITEKNIK LP3I JAKARTA, 2020)
This study aims to find out how the Financial Performance of LP3I Course Center Jakarta in terms of Liquidity, Profitability and Growth ratio. This research uses quantitative descriptive method, that is research conducted by collecting and presenting data received from LP3I Course Center Jakarta in the form of Financial Statement that is Balance Sheet and Profit / Loss Report so as to give clear enough picture for writer to analyze and compare with existing theory. The results showed the financial performance of LP3I Course Center Jakarta is reviewed from Liquidity ratio, shows maximum performance. And Profitability ratio shows the financial performance of LP3I Course Center Jakarta looks unstable marked with the calculation of Operating Profit Margin (OPM) shows financial performance looks good, but Net Profit Margin (NPM) shows the financial performance of LP3I Course Center Jakarta from 2014 and 2015 not yet maximal while in 2016 shows maximum performance. While Return On Investment (ROI) and Return On Equity (ROE) results show the financial performance of LP3I Course Center Jakarta has not looked good yet. And seen from result of growth ratio then LP3I Course Center Jakarta shows maximum financial performance. This can be seen from sales, net operating profit / EBIT, and net income from 2014 to 2016 on average experienced growth.Keywords: Financial Performance, Liquidity Ratio, Profitability, Growth.